Réponses

2013-06-05T23:11:43+02:00

34. a) 2/x = 4/5

: 2 = (4/5)x

: 2*(5/4) = x

: x = 10/4 = 5/2 = 2.5

 

b) 12/(-7) = 3/x

: (12/(-7))x = 3

: x = 3*((-7)/12)

: x = -21/12 = -1.75

 

35. a) (x+2)/6 = -5

: x+2 = -30

: x = -32

 

b) -8 = 12/(2x-3)

: -8(2x-3) = 12

: -16x+24 = 12

: -16x = -12

: x = 12/16 = 3/4 = 0.25

 

36. (x+3)/4 = (5-2x)/3

: (3(x+3))/4 = 5-2x

: (3x+9)/4 = 5-2x

: 3x+9 = 4(5-2x)

: 3x+9 = 20-8x

: 11x = 11

: x = 1

 

37. (3-8x)/(-5) = (-1+7x)/4

: (4(3-8x)/(-5) = -1+7x

: (12-32x)/(-5) = -1+7x

: 12-32x = (-5)(-1+7x)

: 12-32x = 5-35x

: -3x = 7

: x = -(7/3)